Desiring a better country : forays in political theology - Farrow, Douglas, 1953- (Montreal ; Kingston : McGill-Queen's University Press, 2015)
"Desiring a Better Country is a collection of new essays by Douglas Farrow, stimulated by current legal and political and philosophical debates in North America, which challenges the common misconception that secular institutions can be a-theological or religiously neutral. It does so by treating five problems: the grounding of human rights, the dislocation of the goods of marriage, the incoherence of normative pluralism, the uncertain future of religious freedom, and distortions of the libertas ecclesiae or the doctrine of the Two. Conversely, Farrow challenges the notion that the Church can be a-political. The final essay recommends an eschatologically informed solution to the impasse of much post-conciliar political theology, rejecting both the 'social kingship' model and its de-politicized alternative in the later work of John Courtney Murray."--
Includes bibliographical references and index.
Keywords: Political theology; Political theology; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books; Electronic books